Выраженность агрессивности и эмпатии не связана со степенью метисации жителей украинского города - Лучко, Е.Н.; Атраментова, Л.А. (Фактори експериментальної еволюції організмів, 2015)
Aims. Modern megacities characterized by a high degree cross-breeding population. There are only a few information about the effect of cross-breeding on the behavioral traits in the world data bank. Understanding that there is a genetic component in the level of aggression and empathy aims the research to detailed study of those personal characteristics. Methods. 637 men and 856 women (Kharkov citizens) aged 45–65 took part in the research. Assinger’s questionary was used for the study of aggression and Magrabyan-Apstein’s questionary was used for the study of empathy. All the participants gave their informed agreement on questionnaire providing their privacy. Results. The research has shown that the level of cross-breeding of inhabitants of modern Ukrainian city both men and women is not associated with indicators of aggression and empathy. Conclusions. The level of cross-breeding of inhabitants of modern Ukrainian city is not associated with indicators of aggression and empathy. Keywords: empathy, aggression, cross-breeding.